Optimalisasi Audit Kinerja Pemasaran Produk Mayora Melalui Analisis Data Penjualan dan Umpan Balik Konsumen - Siam, Stivenes Tjin; Indah, Nopiani; Santika, Dewi; Suwantono, Edwin; Louw, Febriana (JPM: Jurnal Pengabdian Masyarakat, 2026)
This community engagement program aims to enhance the effectiveness of marketing performance audits at PT Cipta Niaga Semesta, an authorized distributor of PT Mayora Indah Tbk products in West Kalimantan. The main issues faced by the partner company include the suboptimal use of sales data, the unsystematic management of customer feedback, and the high volume of damaged goods, which have not been analyzed as performance indicators. To address these challenges, the academic team from the Faculty of Economics and Business, Widya Dharma Pontianak University, implemented a learning-by-doing mentoring program integrating training, audit simulation, and the analysis of the company’s real operational data. The implementation method consisted of four main stages: preparation, core training, evaluation, and follow-up. Participants were trained to analyze sales trends, identify causes of product damage, design customer satisfaction surveys, and integrate the findings into a comprehensive marketing audit report. The results of the activity showed a significant increase in participants’ understanding, particularly in preparing data-based audit reports (with an improvement of up to 84%). Key findings indicate a negative relationship between the level of damaged goods and customer satisfaction, highlighting the need for a digital system to record returns and store feedback. Through this activity, the company successfully developed an integrated marketing audit template that encompasses sales, logistics, and customer perception data. The mentoring program not only improved staff competencies but also strengthened distribution efficiency and marketing management transparency at both the corporate and retail partner levels.